Planning training Need Analysisto Improve The Competency of Operational Employees at PT. Intra Presisi Indonesia - Nurul Tri Ardiansah; Uli Wildan Nuryanto; Khaeruman Khaeruman (International Journal of Science and Environment (IJSE), 2026)
This study aims to identify the training needs of operational employees at PT Intra Presisi Indonesia through a Training Needs Analysis (TNA) approach that includes organizational analysis, task analysis, and individual analysis. The background of the study is based on the company's training conditions which are still reactive and not yet integrated with long-term human resource development strategies. Data collection was conducted through interviews with management and direct superiors, distribution of questionnaires to operational employees, and review of company documents. The results of the analysis indicate significant competency gaps in the Production, Quality Control, and Maintenance departments. In the Production department, competency gaps were primarily found in the operation of welding robots, die changes, and the application of the 5R principles. In the Quality Control department, the most prominent gaps were in the operation of the Coordinate Measuring Machine (CMM), the application of QC 7 Tools, and root cause analysis. Meanwhile, in the Maintenance department, limited cross-system troubleshooting capabilities and the application of Root Cause Analysis were the main problems. Based on these findings, a training program design was prepared based on competency gap priorities as a basis for developing more targeted, effective, and sustainable training to improve the company's operational performance.